GDP Growth in Russia: Different Capital Stock Series and the Terms of Trade - Ville Kaitila (The Research Institute of the Finnish Economy (ETLA), 2015)
There are different academic assessments as to what lies behind Russia's GDP growth: total factor productivity or fixed capital investments. Studies that reconstruct capital stocks for Russia using gross fixed capital formation and the perpetual inventory method tend to lean towards the former answer, while capital services datasets that have recently been made available lean towards the latter. We reconstruct a capital stock series for Russia for 1995–2013, and compare the results to two capital services time series using the Solow growth model. We also take into account terms of trade developments that have lent strong support to the economy.Finally, we use these tools to construct four possible scenarios for Russia's economic growth up until 2030.
Keywords: 330